Fundamentals of Sintering: Liquid Phase Sintering - de Oro Calderon, Raquel; Gierl-Mayer, Christian; Danninger, Herbert (Reference Module in Materials Science and Materials Engineering, 2015)
Liquid Phase Sintering (LPS) is a versatile tool for producing powder metallurgy components that entails the coexistence of a solid and a liquid phase during sintering. Depending on whether the liquid is present during the whole holding time at sintering temperature or only during a short period in the initial stage, two main variants of the process are possible: persistent or transient liquid phase sintering. Independently of the variant, the main advantage of the formation of a liquid phase is the activation of the sintering mechanisms due to the enhanced mass transport in the liquid as compared to solid-state diffusion. However, the formation of a liquid phase brings some other advantages that are differently exploited in different PM materials. When full density is required, the − typically persistent - liquid phase is used to promote densification by enhancing rearrangement of the powder particles and material redistribution in general and promoting pore closure. On the other hand, in systems where full densification is not aimed at (e.g., PM precision parts) the liquid phase is often of a transient character and can be used as a means to strengthen the sintering contacts and also to obtain tailored microstructures. In this latter case, the liquid can be used as vehicle to distribute the alloying elements in the solid particles, and it is possible to obtain microstructures with tailored inhomogeneity by modifying the infiltrating character of the liquid. This contribution reviews the principles of liquid phase sintering, the evolution of the microstructure as well as some physical, thermodynamic and kinetic concepts of special relevance.